Evaluation of nacelle drag using Computational Fluid Dynamics - Trapp,Luis Gustavo (2010)
Abstract: Thrust and drag components must be defined and properly accounted in order to estimate aircraft performance, and this hard task is particularty essential for propulsion system where drag components are functions of engine operating conditions. The present work describes a numerical method used to calculate the drag in different nacelles, long and short ducted. Two- and three-dimensional calculations were performed, solving the Reynolds Averaged Navier-Stokes (RANS) equations with a commercial Computational Fluid Dynamics (CFD) code. It is then possible to obtain four drag components: wave, induced, viscous and spurious drag using a far-field formulation. An expression in terms of entropy variations was shown and drag for different nacelle geometries was estimated.